2020
DOI: 10.1177/0022343320912816
|View full text |Cite
|
Sign up to set email alerts
|

Mobilizing memories: The social conditions of the long-term impact of victimization

Abstract: Recent research has focused on the legacies of civil war violence on political preferences, finding that wartime victimization decreases support for the perpetrator or its political identity in the long run. However, we know little about the conditions under which this effect takes place. Historical accounts from civil wars suggest that the long-term effect of violence is not homogenous, nor consistent across areas within a single conflict. Addressing this gap, this article explores the effects of wartime vict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
47
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(54 citation statements)
references
References 37 publications
6
47
1
Order By: Relevance
“…The shared experience of high-risk mobilization can forge and consolidate strong social relationships loaded with a sense of mutual trust, and this trust can be transmitted from one generation to the next (Dohmen et al, 2011; Ljunge, 2014; Nunn & Wantchekon, 2011). Such networks play important roles in the sharing and protection of information necessary for organized resistance (Finkel, 2015), and help sustain collective memories that facilitate mobilization later on (Villamil, 2020). Social networks also shape collective notions of threat critical for mobilization decisions (Shesterinina, 2016, p. 422).…”
Section: Violence and Local Ordermentioning
confidence: 99%
“…The shared experience of high-risk mobilization can forge and consolidate strong social relationships loaded with a sense of mutual trust, and this trust can be transmitted from one generation to the next (Dohmen et al, 2011; Ljunge, 2014; Nunn & Wantchekon, 2011). Such networks play important roles in the sharing and protection of information necessary for organized resistance (Finkel, 2015), and help sustain collective memories that facilitate mobilization later on (Villamil, 2020). Social networks also shape collective notions of threat critical for mobilization decisions (Shesterinina, 2016, p. 422).…”
Section: Violence and Local Ordermentioning
confidence: 99%
“…Bracketed in our study—and a fruitful avenue for further research—is how past violence may be used by present-day political elites (c.f. Villamil 2020). Indeed, a follow-up to our study would be to delve into each of these cases to examine whether and how, over time, wartime victimization and participation have been memorialized and politicized and with what effect on popular perceptions, including views on peace agreements.…”
Section: Discussionmentioning
confidence: 99%
“…A long-standing body of research has shown that experiences of violence shape people’s political behavior and attitudes even long after a conflict ends (e.g., Dyrstad et al 2011; Brounéus 2014; Gilligan, Pasquale, and Samii 2014; Nussio and Oppenheim 2014; Hall et al 2018; Hong and Kang 2017; De Juan and Pierskalla 2016)—even across generations (e.g., Balcells 2012; Lupu and Peisakhin 2017; Rozenas and Zhukov 2019; Costalli and Ruggeri 2019; Villamil 2020). 2 Warfare is likely to generate both psychological and material grievances: trauma or disability from one’s own experiences of violence (either as a victim or perpetrator or both), the loss and victimization of loved ones, and loss of one’s home and income (e.g., Justino 2009; Gates et al 2012).…”
Section: Argument: the Long-term Legacies Of Wartime Violencementioning
confidence: 99%
“…One possibility is that in testing for the effects of 'victimization' , broadly conceived, researchers are masking substantial heterogeneity among different types of victimization experiences. For instance, there is mixed evidence that suggests victimization effects can change over time (Balcells, 2012;Rohner, Thoenig and Zilibotti, 2013;Villamil, 2020). The context in which victims find themselves can also moderate the impact of victimization: scholars have documented how wars can create "hierarchies of victimhood" that make some victims more likely to mobilize and participate than others (Berry, 2017) and that patterns of rebel governance can impede or mobilize victim activism (e.g.…”
Section: The Effects Of Victimization On Social Cohesionmentioning
confidence: 99%